2012
DOI: 10.1038/bjc.2012.148
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer incidence in young women: a historical and geographic controlled UK regional population study

Abstract: Background:The commencing age of cervical screening in England was raised from 20 to 25 years in 2004. Cervical cancer incidence in young women of England is increasing. It is not clear if this is due to either greater exposure to population risk factors or reduced cervical screening.Methods:We measured if the relative risk of cervical cancer in younger women (20–29 years) of the north-east of England (NE) differed to that of women aged 30yrs and above since 2004. We also measured average annual percentage cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 18 publications
2
32
0
2
Order By: Relevance
“…Although the incidence of cervical carcinoma in Korean females of all ages is decreasing (APC  =  −4.3%) [6], the incidence of cervical carcinoma has been increasing among Korean females under 30 years of age [30]. A steady increase in cervical carcinoma in young women (20–29 years) has also been observed in England [31]. The increased incidence of cervical carcinoma among AYAs has been attributed to increases in human papillomavirus (HPV) infection [32], [33].…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of cervical carcinoma in Korean females of all ages is decreasing (APC  =  −4.3%) [6], the incidence of cervical carcinoma has been increasing among Korean females under 30 years of age [30]. A steady increase in cervical carcinoma in young women (20–29 years) has also been observed in England [31]. The increased incidence of cervical carcinoma among AYAs has been attributed to increases in human papillomavirus (HPV) infection [32], [33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of cervical cancer in women aged 20–29 in the United Kingdom are few and tend to be small (Rieck et al , 2006; Nair et al , 2007; Herbert et al , 2008; Patel et al , 2012). The combined results for all but the largest study include a total of just 18 cancers (all of which were in women offered screening from age 20 years) diagnosed at age 20–24 years.…”
Section: Discussionmentioning
confidence: 99%
“…Over 60% of cancers in these studies were stage 1A and roughly the same proportions were found to be screen detected. The largest study by Patel et al (2012) included 152 cases aged 20–29 years diagnosed over a 10-year period in the north east (NE) of England. They found a much higher proportion of cancers at age 20–24 years (26%) than found in this national study (12%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent increase in invasive carcinomas in women aged 25-29 years, and to a lesser extent aged 30-34 years, appears to be related to a 'cohort effect' of young women at an increased risk of the disease. 24 Most of the cancers in women aged 20-29 years were detected by cytological screening at an early stage, particularly when microinvasive (stage IA), which may partly be a result of delaying the first screening invitation to age 25. 25 Whatever the cause of the increased rates of CIN3 and cancer, primary HPV testing, as proposed in England, would be introduced in a population with a higher prevalence of disease than ever recorded before in young women: 14 273 cases of CIN3/AIS and 464 cancers were registered in women below 30 years of age in 2013.…”
Section: High Prevalence Of Cin3 and Screen-detected Cancer In Young mentioning
confidence: 99%